ANALISIS KINERJA KECAMATAN KEJAKSAN KOTA CIREBON - Purbasari, Diah Ayu; Suwitri, Sri; D, Ida Hayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Organization formed to achieve goals. The success of organization in achieving the goals determined by how the performance of the organization. Organizational performance is the result of cooperative activities between the components of organization in order to realize the goals of the organization. Subdistrict is an agency which has the task of regional technical implementation under the regency or city. Cirebon City have five districts and Kejaksan District has achievement with lowest strategic target. The purpose of this study is to analyze the performance of Kejaksan District and analyze aspects that support and obstacle the performance of Kejaksan District Cirebon City. Kejaksan District analyzed the performance by the dimensions of productivity and fairness. Productivity Kejaksan District of Cirebon City has not been achieved realization of the programs and activities with the planned target. Kejaksan District of Cirebon City not attention to justice for society as seen from the activities and the amount budget allocations for the public is smaller than for the internal of Kejaksan District. According to dimensions researched, it can be concluded if the performance of Kejaksan District is not optimal. Aspect that support the performance of Kejaksan District is leadership and obstacle aspects are human resources, society participation, and budget. Based of obstacle aspects, the author give advice for increasing employee volunteers, make programs or activities that are more innovative in order to increase public participation, and Kejaksan District should give more attention for budget allocation between internal and society.